2002
DOI: 10.1074/jbc.m110013200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 Gene Expression Is Regulated by GATA-3 in T Cells

Abstract: Using a transgenic approach, we studied the role of GATA-3 in T cells. As previously shown, enforced GATA-3 expression in transgenic mice inhibits Th1 differentiation of CD4 T cells, but unexpectedly, both type 1 (interferon ␥) and type 2 (interleukin (IL)-4 and IL-13) cytokine genes were activated in the transgenic CD8 T cells. Because IL-13 gene expression was highly enhanced in vivo by GATA-3 expression, we studied the human and the mouse IL-13 gene promoters and found an evolutionary-conserved association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…The production of Th2 cytokines, particularly IL-5 and IL-13, were reported to be highly dependent on the transcriptional activity of GATA3 (16,35,36). We reported that expression of GATA3 induced more than a 10-fold increase in IL-5 and IL-13 promoter activities, whereas that of the IL-4 promoter was increased only about 2-fold (23).…”
Section: Discussionmentioning
confidence: 68%
“…The production of Th2 cytokines, particularly IL-5 and IL-13, were reported to be highly dependent on the transcriptional activity of GATA3 (16,35,36). We reported that expression of GATA3 induced more than a 10-fold increase in IL-5 and IL-13 promoter activities, whereas that of the IL-4 promoter was increased only about 2-fold (23).…”
Section: Discussionmentioning
confidence: 68%
“…This may account for the great amounts of Th2 cytokine production including IL-13 and IL-5 (Fig. 2), whose transcription is highly sensitive to GATA3 (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3). The transcription of IL-5 and IL-13 is known to be highly dependent on GATA3 as compared with that of IL-4 (11,48,49). An efficient transcription of IL-5 or IL-13 may require the enhanced levels of GATA3 that can be achieved by the presence of CD28-costimulation.…”
Section: Discussionmentioning
confidence: 99%